Adaptation of Global Organizational Cultural Diversity in McDonald's Multinational Company at the Local Level - Arif Rahman; Amellia Enggellina; Afilda Kilani; Dian Prihardini Wibawa (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the adaptation of global organizational culture in the context of multinational companies, specifically in the case of McDonald's Indonesia. Globalization encourages multinational companies to integrate international operational standards with local cultural values ​​through a glocalization strategy to increase market acceptance and business sustainability. This study uses a qualitative approach with content analysis methods on secondary data derived from company reports, academic publications, and literature related to cross-cultural management. The theoretical basis of the research refers to Geert Hofstede's national cultural dimensions and the concept of Cultural Intelligence by Christopher Earley and Soon Ang. The results indicate that organizational culture adaptation at McDonald's in Indonesia is achieved through the integration of the company's global values ​​with local cultural preferences, encompassing product innovation, organizational communication, human resource management, and stakeholder relationship strategies. The glocalization strategy enables the company to maintain its global brand identity while increasing social and cultural relevance in the local market. The research findings indicate that cultural intelligence and management flexibility are critical factors in the success of multinational companies, as managing an inclusive and adaptive organizational culture can increase employee loyalty, the effectiveness of cross-cultural communication, and the company's competitiveness in the era of globalization.